Theory of Preferences : Methodology, Modeling, and Analysis - Krautwurm, Petr (2026)
This dissertation revisits two core themes in the theory of preferences, each with direct relevance for welfare reasoning and for applied decision work: higher-order preferences and relationships between aspects of actions. The thesis is explicitly interdisciplinary, with a guiding aim of conceptual clarification at the level of foundational principles and definitions. Regarding higher-order preferences, the dissertation clarifies what it means to want something once preferences may vary across time and current selves oppose these variations, and how it relates to welfare claims. Regarding relationships between aspects of actions, it clarifies what it means that aspects of action are related -- in particular, what it means for products to be substitutes or complements -- given that intuitive notions are often preference-based while most operational definitions are market-based, and these need not coincide. In doing so, the thesis connects (i) economics and philosophy, where the central task is to delimit welfare-relevant preference structure under preference variation; (ii) econometrics, where the focus is on observability and identification of such structure; and (iii) policy studies and operations research, where the objective is to make these objects usable in applied design and decision work. The thesis consists of five papers.